Greek traditional architecture. Kozani - Αυγερινού-Κολώνια, Σοφία (Library of art, 1990)
The 55 books of the series give historical, architectural and cultural information on the different areas and islands of Greece.The objective of the series is to gather and present scattered material which has remained unpublished so as to give a complete picture of each area.